Contribution of Sub-Saharan African medicinal plants to cancer research: Scientific basis 2013-2023 - Marc D.W. Adico; Bagora Bayala; Julio Bunay; Silvère Baron; Jacques Simpore; Jean-Marc A. Lobaccaro (Elsevier, 2024)
Cancer incidence and mortality rates are increasing worldwide. Cancer treatment remains a real challenge for African countries, especially in sub-Saharan Africa where funding and resources are very limited. High costs, side effects and drug resistance associated with cancer treatment have encouraged scientists to invest in research into new herbal cancer drugs. In order to identify potential anticancer plants for drug development, this review aims to collect and summarize anticancer activities (in vitro/in vivo) and molecular mechanisms of sub-Saharan African medicinal plant extracts against cancer cell lines. Scientific databases such as ScienceDirect, Google Scholar and PubMed were used to search for research articles published from January 2013 to May 2023 on anticancer medicinal plants in sub-Saharan Africa. The data were analyzed to highlight the cytotoxicity and molecular mechanisms of action of these listed plants. A total of 85 research papers covering 204 medicinal plant species were selected for this review. These plants come from 57 families, the most dominant being the plants of the family Amaryllidaceae (16), Fabaceae (14), Annonaceae (10), Asteraceae (10). Plant extracts exert their anticancer activity mainly by inducing apoptosis and stopping the cell cycle of cancer cells. Several plant extracts from sub-Saharan Africa therefore have strong potential for the search for original anticancer phytochemicals. Chemoproteomics, multi-omics, genetic editing technology (CRISPR/Cas9), combined therapies and artificial intelligence tools are cutting edge emerging technologies that facilitate the discovery and structural understanding of anticancer molecules of medicinal plants, reveal their direct targets, explore their therapeutic uses and molecular bases.